Significance of direct and indirect pollination ecosystem services to the apple industry in the Western Cape of South Africa - Mouton, Madele (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScConEcol (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.